PENGARUH MEDIA WEB ENHANCED COURSE TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI MAN 1 PRABUMULIH - Desi Safitri; Riswan Jaenudin; Deskoni Deskoni (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2015)
This study aims to determine whether or not there is an enhanced web media influence the course of the learning outcomes of students in economic subjects in MAN 1 Prabumulih. This study design using pre-experimental design in the form of one - group pretest-posttest design. The population in this study were all students of class X MAN 1 Prabumulih semester 2014/2015 academic year consisting of six classes ie 4 grade 2 class IIS and MIA. Sample selection techniques using random cluster sampling, the chosen one class taken through a lottery to be selected as the study sample, the elected class is a class X. IIS 1, which consists of 29 students. Data collection techniques obtained using tests and observation. Observation was used to observe the learning process takes place. The statistics are used to analyze the data in the proof using the formula t-test, with significance level α = 5% (0.05), and dk = n - 2 so (df = 29-2 = 27) was 1,703, the results of hypothesis testing obtained thitung> table = 4.366> 1.703. If thitung> ttabel makaHo rejected Ha accepted. So the conclusion is no difference in the effect of enhanced web media course on learning outcomes of students in economic subjects in MAN 1 Prabumulih. It can also be seen from differences in learning outcomes of students before and after the treated media web enhanced course with the increase in the average value of a low of 37, with 26 during pretest increased menjadi 63 during the posttest, the increase is also contained in the value of the highest rates of 26 is 73 during the pretest and increased to 96 during the posttest. Therefore, it is advisable for teachers to implement the enhanced web media in the course of learning as an alternative teachers to improve student learning outcomes.